2011
DOI: 10.1016/j.micinf.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive and critical roles for cellular immunity and immune-inflammatory response in the immunopathology of Sendai virus infection in mice

Abstract: Overall, DBA/2J mice exhibited a dysregulated hyper-inflammatory cytokine/chemokine cascades that does not limit viral spread resulting in a predisposition to severe lung pathology. This response is similar to severe human respiratory paramyxovirus infections, which will serve as a model for the elucidation of hyper-immune inflammatory response that result to severe immunopathology in respiratory viral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…As has been previously described, DBA/2 mice are highly susceptible to lethal infection with SeV [11,13-15]. Specifically, we found that DBA/2 mice which received a higher titer virus inoculum (1.6x10 5 IU of SeV) sustained greater weight loss and mortality than the mice that received the lower inoculum (1.6x10 3 IU of SeV).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As has been previously described, DBA/2 mice are highly susceptible to lethal infection with SeV [11,13-15]. Specifically, we found that DBA/2 mice which received a higher titer virus inoculum (1.6x10 5 IU of SeV) sustained greater weight loss and mortality than the mice that received the lower inoculum (1.6x10 3 IU of SeV).…”
Section: Discussionsupporting
confidence: 79%
“…Differences in susceptibility to SeV infection among mouse strains exist, with C57BL/6 mice being more resistant and DBA/2 mice being more susceptible to infection [11,13,14]. SeV is known to be a strong inducer of various cytokines/chemokines, including interferon-Υ, IL-2, TNF-α, IL-6, and IL-10 [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus preparations were evaluated for purity by electron microscopy and quantified using a latex sphere standard as previously described. 28 To derive the virus particle number per milliliter using an alternate method that was determined comparable to electron microscopy, total viral RNA was extracted for quantitative reverse transcription-polymerase chain reaction (qRT-PCR) analysis 29 using the reported molecular weight of the genome RNA (3.3 3 10 6 ). The DENV viability was measured by Vero cell infectivity using standard plaque assays.…”
Section: Denv Purificationmentioning
confidence: 99%
“…Two-step qRT-PCR was conducted as previously described 29 except DENV RNA was extracted from homogenized platelet pellets using TRIzol reagent. DENV RNA was purified with RNeasy Micro Kit and further incubated with Turbo DNase to digest and eliminate DNA.…”
Section: Dengue Virus Rna Quantificationmentioning
confidence: 99%